Association Between the Triglyceride-Glucose Index and Peripheral Artery Disease: A Meta-Analysis - Zhao, Lei; Wei, Lan; Fei, Xiao-Lu (Hormone and Metabolic Research)
The triglyceride-glucose (TyG) index, an indicator of insulin resistance, has emerged as a potential predictor of various cardiovascular diseases. However, the association between the TyG index and peripheral artery disease (PAD) remains unclear. This meta-analysis sought to clarify the relationship between the TyG index and the incidence or prevalence of PAD. A comprehensive search of the PubMed, Embase, and Web of Science databases was carried out to identify relevant observational studies published up to June 1, 2024. Inclusion criteria included studies on adult populations that evaluated the TyG index and reported PAD outcomes. To assess the association between the TyG index and PAD, risk ratios (RRs) and 95% confidence intervals (CIs) were computed using a random-effects model incorporating the impact of heterogeneity. Nine studies with a total of 37,761 participants were involved in the meta-analysis. The analysis revealed that individuals with a high TyG index had significantly increased odds of PAD (RR: 1.42, 95% CI: 1.21–1.67, p < 0.001; I² = 55%). Sensitivity analyses performed by excluding one study at a time confirmed the robustness of these findings. Subgroup analyses demonstrated consistent associations across different study designs, populations, and methodological quality. Diabetic patients exhibited a stronger association (RR: 1.38) compared to non-diabetic participants (RR: 1.06, psubgroup difference = 0.006). In conclusion, a high TyG index is linked to PAD, especially in people with diabetes. These results suggest that the TyG index could be used as a valuable marker for assessing PAD risk in clinical practice.